Simulation of radiation performance for mobile antennas using a hybrid fem-fdtd computational technique - Alias, Rozlan (2011)
The objective of this paper is to study the radiation performance of mobile handsets antenna by using the hybrid method between the Finite-Element Method (FEM) and the Finite Difference Time Domain (FDTD), as applied to computational electromagnetic studies, e.g. antenna scattering modelling problems. An application of modified equivalent surface boundary using the hybrid FEM-FDTD technique [1] is presented and discussed in terms of the memory locations and processing time required for updating the equivalent surface currents from FEM to FDTD methods. A reduced equivalent surface size that encloses the radiating part of the antenna is studied and the results are compared with different sizes of the equivalent surface configurations. Several examples are presented and the results were stable and quite reasonable with published data.